[18F]-THK5351 PET Imaging in Patients With Semantic Variant Primary Progressive Aphasia. (January 2018) - Lee, Hyon; Seo, Seongho; Lee, Sang-Yoon; Jeong, Hye Jin; Woo, Sung-Ho; Lee, Kyoung-Min; Lee, Yeong-Bae; Park, Kee Hyung; Heo, Jae-Hyeok; Yoon, Cindy W.; Kang, Jae Myeong; Cho, Jaelim; et al.
Abstract : Background: Semantic variant primary progressive aphasia (svPPA) has been associated with a variety of proteinopathies, mainly transactive response DNA-binding protein, but also with tau and β-amyloid. Recently selective tau tracers for positron emission tomography (PET) have been developed to determine the presence of cerebral tau deposits in vivo. Here, we investigated the topographical distribution of THK5351 in svPPA patients. Materials and Methods: Five svPPA patients, 14 Alzheimer's disease patients, and 15 age-matched normal controls underwent [ 18 F]-THK5351 PET scans, magnetic resonance imaging, and detailed neuropsychological tests. [ 18 F]-fluorodeoxyglucose PET was obtained in 3 svPPA patients, whereas the remaining 2 underwent amyloid PET using [ 18 F]-flutemetamol. Tau distribution among the 3 groups was compared using regions of interest–based and voxel-based statistical analyses. Results: In svPPA patients, [ 18 F]-THK5351 retention was elevated in the anteroinferior and lateral temporal cortices compared with the normal controls group (left>right), and in the left inferior and temporal polar region compared with Alzheimer's disease patients. [ 18 F]-THK5351 retention inversely correlated with glucose metabolism, whereas regional THK retention correlated with clinical severity. [ 18 F]-flutemetamol scans were negative for β-amyloid. Conclusions: These findings show that [ 18 F]-THK5351 retention may be detected in cortical regions correlating with svPPA pathology. Abstract : Supplemental Digital Content is available in the text.